Relationship between Macroeconomic Policy and Long-Run Economic Growth of Nepal (Quest Journal of Management and Social Sciences, 2021)
Background: The paper is an attempt to find the long-run relationship between macroeconomic variables and economic growth in Nepal. The variables in the study are run across the Cobb-Douglas production model.Objective: This paper examines the relationship between Gross Fixed Capital Formation, Population, Trade openness, Money Supply and GDP growth economic growth in Nepal.Method: The ARDL bound test and Error Correction model incorporated in the study to examine the long-run relationship among macroeconomic variables.Conclusion: Based on the Bound Test of F-statistics the Cointegration Result exists among the variable and ARDL (1,1,1,1,1) relation is estimated.Implications: Since the study has found the existence of a cointegration relationship on the variables of the study and the long-term relationship among economic growth is significant with GFCF. The policy should be targeted at investment growth in Nepal.